Clinical outcome of clip-less cholecystectomy versus conventional laparoscopic cholecystectomy - Ahmed, Hiwa Omer; Muhamad, Ara (Advances in Social Sciences Research Journal, 2015)
Abstract Background: Laparoscopic cholecystectomy is the gold standard worldwide in the surgical treatment of cholecystitis and symptomatic gallstone because it gives well known and more definite advantages if compared with the open procedure. The traditional Laparoscopic cholecystectomy is usually performed by mean of the dissector, the electrosurgical hook, spatula and /or scissor, this method has been used in most centers. Now Harmonic scalpel is used widely to include surgery of head and neck, chest and liver, spleen kidney, adrenal glands colon, rectum and others. Aim: We present this paper in a trial to evaluate the safety, efficacy and clinical outcome of Laparoscopic cholecystectomy using harmonic scalpel for securing cystic duct and artery compared with conventional laparoscopic cholecystectomy. Patients and method: Prospective interventional study was carried out from 1st February 2012 to 14th January 2013, 60 patients were included by laparoscopic cholecystectomy for symptomatic gallstone disease at Slemani Teaching Hospital. The primary outcome was the duration of the operation .the second outcome was the conversion rate .The third outcome was perforation of gallbladder during dissection .the fourth outcome was bleeding during the operation and all were reported intra operatively. All possible complications and clinical outcomes in 30 days period compared in both groups. Results: This study was conducted in a period from 1st February 2012 to 14th January 2013, during this time sixty patients were included to this prospective randomized study, the patients were divided in to two groups each with 30 patients with the mean age 39.0 ranging from 22 to 66 years. They were 85 % female and the remainder were males with non-significant results statistically regarding age and gender. We found; The mean operative time was (33.17±8.23) in group A and (18.53±2.37) in group B ; p = ˂0.001, The incidence of gall bladder perforation was 43.33% in group A and 13.33% in group B; p= 0.010, The incidence of pain at 24 hour postoperatively is significantly more in group A compared with group B; p= 0.021. Conclusion: We found that harmonic scalpel cholecystectomy is comparable to conventional laparoscopic cholecystectomy in, shortening the time of the procedure and has less sequels and complications in comparison to conventional laparoscopic cholecystectomy. Key Words: Conventional laparoscopic cholecystectomy, harmonic scalpel laparoscopic cholecystectomy, pain, gallbladder perforation and duration of operation.